KEBIJAKAN HAMBATAN EKSPOR BIJI KAKAO INDONESIA TAHUN 2010 - Shoni, Tedisah; Jamaan, Ahmad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
This research analyzes the policy issues set by the Republic of Indonesia regarding Barriers to Cocoa Bean Exports as a step to channel domestic cocoa beans to national cocoa processing factories. Indonesia, as a cocoa bean producing country, exports cocoa beans from its plantations to various continents throughout the world. The government plans to limit exports of Indonesian cocoa beans because it would be more profitable if Indonesia developed its own cocoa processing factory so that later, what was originally exporting cocoa beans could become a country that exports processed cocoa which has a higher price value than cocoa beans which are only raw materials. This research uses neo-mercantilism theory at the nation-state level of analysis. This research uses qualitative methods and data collection techniques carried out through books, journals, websites and articles. Through this research, the conclusion was obtained that the Republic of Indonesia Policy Regarding Barriers to Cocoa Bean Exports has had a positive impact on the profits and development of Indonesian cocoa trade in the international market. Some of the benefits obtained from this policy include: New job opportunities have opened up in the country due to the growing cocoa processing industry. Considerable added value has been obtained from processed cocoa exports since Indonesia implemented a policy of restricting cocoa bean exports. Keywords : cocoa, exports, Indonesia, policy, world